164k views
1 vote
Solve the system of equations step by step also you can use any method to solve this I just need help

X+2y=2 and -x+y=-5

User Aravind NC
by
4.8k points

2 Answers

4 votes

Answer: x = 4

y = -1

Explanation:

Elimination Method:

In an elimination problem, both equations are aranged in the form of an arithmetic problem. One equation must have an offset of either the x or y of the other equation, so as to eliminate the variable for you to solve for the other one. If a variable doesn't have a negative counterpart, multiply the equation by a number so they can offset each other.

Given:

x + 2y = 2

-x + y = -5

Step 1: Solve for x

To solve for x, we need to eliminate the y by creating an equation where the y can eliminate the other equations y.

-2(-x + y = 5) = 2x - 2y = 10

Now that the y's can cancel each other out, we can combine the equations and solve for x.

x + 2y = 2

2x - 2y = 10

3x = 12

x = 12/3

x = 4

This is the value of x

Step 2: Solve for y

The x's can already cancel each other out, so you can just combine the equations and solve for y.

x + 2y = 2

-x + y = -5

3y = -3

y = -1

This is the value of y

Step 3: Verify

To make sure there weren't any mistakes, you need to check by replacing x and y with they're values. x is 4 and y is -1

Substitute: (4) + 2(-1) = 2

Solve: 4 - 2 = 2

Substitute: -(4) + (-1) = -5

Solve: -4 - 1 = -5

The answers are x = 4 and y = -1

User Harsha Vardhini
by
5.1k points
3 votes

Answer:

Solution :

{x,y} = {2/3,2/3}

Explanation:

Solve equation [2] for the variable x

[2] 9x = 6

[2] x = 2/3

// Plug this in for variable x in equation [1]

[1] (2/3) + 2y = 2

[1] 2y = 4/3

[1] 6y = 4

// Solve equation [1] for the variable y

[1] 6y = 4

[1] y = 2/3

// By now we know this much :

x = 2/3

y = 2/3

(I dunno if this is what you meant or not..)

User Emil Salageanu
by
4.9k points